Dinamika Komunikasi Awal Perempuan Pengguna Bumble: Strategi dan Faktor Keberhasilan - Chrysantia, Adelya; Junaidi, Ahmad (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2026)
This study analyzes the success of women's initial interactions on the Bumble dating app amid advancements in information and communication technology that are transforming digital interpersonal communication, particularly through the unique